COMPARISON OF FUEL CONSUMPTION AND EMISSION OF SMALL TWO-STROKE ENGINE OF ELECTRIC GENERATOR FUELLED BY METHANOL, BIOGAS, AND MIXED METHANOL-BIOGAS - Dana, I Wayan Agus Rantia; Lie, David; Adnyana, I Wayan Bandem; Nindhia, Tjokorda Gde Tirta; Khanal, Samir Kumar; Nindhia, Tjokorda Sari (Journal of Applied Engineering Science, 2022)
A two-stroke engine run with flexible fuel of biogas or methanol is not established yet. It is the objective of this work to provide 2 stroke engine for an electric generator that can be run by using flexible fuels namely: methanol, biogas, and mixed methanol-biogas. A small single cylinder 2 stroke engine of an electric generator was set to be able to be fuelled by using 3 different types of fuel namely biogas (50% vol. CH4, 15% vol. CO2, 0 ppm H2S), methanol (CH3OH) with 97% vol. purity and mixed biogas-methanol. The electric generator that is used is for providing 750-watt electricity. The compression pressure was around 10 Bar with cylinder volume around 63 cc. The engine was set with an easy switch system of fuel. Since methanol is used as one type of fuel that is used, then special lubricant should be prepared for this purpose. It is generally known that commercial synthetic lubricant that is usually used and mixed with gasoline for 2-stroke engines is found not well mixed with methanol. The castor oil is selected to be used as a lubricant to be mixed with methanol with a ratio of methanol to castor oil of 50:1. During using only biogas as a fuel, the castor oil was dripped around 3 drops/minute in the biogas-air mixer chamber. The emission, as well as fuel consumption, were investigated both in idle position and loaded at 200 watts. It is found that for only biogas fuel, the fuel consumption is 18.83 L/minute and increases to become 15, 17 L/minute at a load of 200 watts. By using only methanol as a fuel, the fuel consumption is found 0.009 L/minute and increases to become 0.011 during loading at 200 watts. If mixed fuel is applied the biogas consumption becomes 2.06L/minute in idle position and 4.43 L/minute at a load of 200 watts. The lowest CO emission in idle position was found with biogas as fuel at 0.18 % vol., followed by mixed fuel biogas+ methanol at 0.26% vol. and the highest is methanol fuel at 0.25%vol. for a load of 200 watts, the lowest CO emission is found the same at biogas fuel at 0.18% vol., followed by mixed biogas + methanol at 0.011 % volume, and the worst is found for methanol fuel with CO emission of 0.33 % vol.